2010
DOI: 10.1021/nn901869f
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Response to Gold Nanoparticles

Abstract: See the accompanying Perspective by Albanese et al. on p 2490.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
237
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(243 citation statements)
references
References 62 publications
6
237
0
Order By: Relevance
“…Also at doses from 0.2 mg/mL, for hexagonal GNPs, the Factin cytoskeleton was found deformed, caspases activity (indicates the strong activation of both intrinsic and extrinsic apoptotic pathways) increased and the expression of lysosomal enzyme Cathepsin-B heightened. The onset of apoptotic cell death within Calu-3 epithelial cells over the 72 hour exposure period to hexagonal GNPs can further be associated with the significant increase in non-mitochondrial ROS production since the induction of cell death can be elucidated by an increase in ROS, and are in support of the findings of a recent study by Hutter et al [6].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also at doses from 0.2 mg/mL, for hexagonal GNPs, the Factin cytoskeleton was found deformed, caspases activity (indicates the strong activation of both intrinsic and extrinsic apoptotic pathways) increased and the expression of lysosomal enzyme Cathepsin-B heightened. The onset of apoptotic cell death within Calu-3 epithelial cells over the 72 hour exposure period to hexagonal GNPs can further be associated with the significant increase in non-mitochondrial ROS production since the induction of cell death can be elucidated by an increase in ROS, and are in support of the findings of a recent study by Hutter et al [6].…”
Section: Discussionsupporting
confidence: 85%
“…Due to their plasmonic properties, gold nanoparticles (GNPs) have been proposed as advantageous nano-sized materials for use in the various diagnostic and therapeutic applications, such as cell imaging, targeted drug delivery, thermal ablation, phototherapy [1][2][3][4][5][6][7].. To date spherical GNPs have been proven as one of the most biocompatible NP models for biological-based applications [8][9][10][11][12]. Recently, it has been reported that the specific shape of GNPs can be exploited to advantageously tune these nanomaterials for any biomedical application of choice [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…This is different from other metal-based nanoparticles, including zinc and titanium oxide nanoparticles that have substantial toxicity in neurons and astrocytes. [26][27][28] Compared to these other metal nanoparticles, the IONP-based compositions used in the present study appear to have good biocompatibility with concentrations required to produce toxicity being rather large and not likely to be obtained in vivo or in clinical applications. 11,29 We had hypothesized that the extent of nanoparticle accumulation in cells would have important implications in the extent of potential toxicity produced.…”
Section: Discussionmentioning
confidence: 96%
“…The bEnd.3 cells (passage number [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were cultured in Dulbecco's Modified Eagle Medium (DMEM) (Hyclone, Logan, UT) supplemented with 10% heat-inactivated fetal bovine serum (FBS; Hyclone), 50 U/ mL penicillin and streptomycin (MP Biomedicals, Solon, OH, USA) at 37°C and 5% CO 2 . Cells were expanded in T-75 tissue culture flasks and seeded at 2 × 10 4 cells per cm 2 on six-or twelve-well plates for uptake and cytotoxicity studies, respectively.…”
Section: Cell Culturementioning
confidence: 99%
“…Importantly, the geometry of GNPs, such as rods, shells, cages, or branched particles, not only impacts their LSPs but also alters their interaction with the bio-environment, and is thus critical to nanoparticle uptake and toxicity [17][18][19][20]. In addition to properties of the GNP, the cell type is also a determining factor in the bio-nano interaction [20].…”
Section: Introductionmentioning
confidence: 99%